Hidden attraction : the history and mystery of magnetism - Verschuur, Gerrit L., 1937- (Oxford University Press, 1996)
In Hidden Attraction Gerrit L. Verschuur traces the history of our fascination with magnetism, from the first discovery of magnets in Greece, to state-of-the-art theories that see magnetism as a basic force in the universe.